M267 Health Status And Quality Of Life In Idiopathic Pulmonary Fibrosis And Sarcoidosis: Effect Of Fatigue. (10th November 2014) - Atkins, CP; Gilbert, D; Brockwell, C; Robinson, S; Wilson, AM
Abstract : Introduction and Objective: Sarcoidosis and Idiopathic Pulmonary Fibrosis (IPF) are two common forms of interstitial lung disease. Sarcoidosis frequently causes extra-pulmonary disease whereas IPF specifically affects the lungs. Fatigue is a common feature of sarcoidosis, but an association between fatigue and IPF has not been investigated. We investigated the frequency and severity of fatigue in sarcoidosis and IPF, how it correlates with quality of life (QOL) scores, and whether fatigue is affected by disease severity. Methods: This was a cross-sectional questionnaire study of patients with sarcoidosis and IPF. Questionnaire data was analysed to investigate health status, QOL, and symptom prevalence (fatigue, depression and sleepiness). Comparison of scores between groups, and an analysis of the effect of markers of disease severity on fatigue, was undertaken. Results: Questionnaires were administered to 235 participants; 82 healthy volunteers, 76 sarcoidosis patients and 77 IPF patients. IPF patients had statistically higher St George's Respiratory Questionnaire (p = 0.034) and Epworth Sleepiness Scale scores (p = 0.003) than sarcoidosis patients, but there was no difference in mean fatigue scores. When stratified by questionnaire scores (Table 1 ), including pathological fatigue levels, no statistical difference was seen between IPF and sarcoidosis, although there was a trend towards a higher frequency of 'severe fatigue' in sarcoidosis. Fatigue scores correlated strongly with quality of life scores (King's Brief Interstitial Lung Disease score and St George's Respiratory Questionnaire) in both IPF ( r =-0.615 and 0.659 respectively) and sarcoidosis ( r =-0.529 and 0.502). In sarcoidosis, no measures of dyspnoea or disease severity (spirometry abnormality, immunosuppression use or extrapulmonary disease) were associated with fatigue scores. In IPF increasing dyspnoea scores were associated with increased fatigue scores (p < 0.001). Conclusions: Both sarcoidosis and IPF patients suffer with high levels of fatigue, although the sarcoidosis cohort showed a trend towards greater frequency of severe fatigue compared with IPF. In IPF patients increasing fatigue was associated with worsening dyspnoea, suggesting an association with disease progression, but no similar relationship was seen in sarcoidosis. This suggests that fatigue in sarcoidosis occurs independently of common markers of disease activity, whereas it occurs as a sequelae of progressive disease in IPF.